IMMOBILIZATION OF Saccharomycess cereviceae BIOMASS ON CHITOSAN AND ITS APPLICATION AS AN ADSORBENT FOR Pb(II) ION - Hasri Hasri; Mudasir Mudasir; Nurul Hidayat Aprilita; Roto Roto (Universitas Gadjah Mada, 2011)
An application of Saccharomycess cereviceae biomass immobilized on chitosan (SC-Chi adsorbent) for Pb(II) ion removal was demonstrated. Adsorption experiment was conducted at various mass ratio of Saccharomycess cereviceae biomass to chitosan, contact time, pH of solution and concentration of cation. Total Pb(II) metal ion adsorbed was calculated from the difference of the amount of metal ion before and after adsorption which was measured by AAS. The results showed that optimum condition for adsorption of Pb(II) ion by the SC-Chi was achieved using mass ratio of Saccharomycess cereviceae to chitosan of 50% (w/w), pH solution of 7, contact time of 60 min and concentration of 25 mgL-1. The hydroxyl (-OH) and amino (-NH2) functional groups are believed to be responsible for the adsorption of Pb(II) ion by the adsorbent.